O35 Spatial and temporal associations between sexually transmitted and recent congenital syphilis cases in england. (8th June 2017) - Furegato, Martina; Fifer, Helen; Vanta, Paul; Mohammed, Hamish; Simms, Ian; Logan, Louise; Gill, Noel; Charlett, Andre'; Hughes, Gwenda
Abstract : Introduction: Four infants with congenital syphilis (CS) born to UK-born mothers who screened syphilis negative at first trimester antenatal screen were identified in England between March2016–January2017. Simulation modelling using historic data suggested the probability of observing these events was about 1%. We assessed whether these recent CS cases were associated with underlying epidemiology of infectious syphilis (IS). Methods: Data from 01/2011–09/2016 were obtained from GUMCADv2, the national STI surveillance system in England. We defined three syphilis epidemiological areas (SEAs): wider incident areas (WIAs; the affected and immediate surrounding counties); endemic areas (established epidemics in men who have sex with men-MSM); non-incident/non-endemic areas (NINEAs). IS rates/100, 000 population were derived and associations between IS characteristics and SEAs were assessed using bivariate analyses. Mothers of CS cases were excluded from analyses. Results: From 2011–2016, IS rates/100, 000 in WIAs rose in heterosexual women (1.5–2.5, 67% increase) and MSM (9.0–13.7, 52% increase) but fell in heterosexual men (4.3–2.7, 37% decrease). In NINEAs, rates rose in heterosexual women (1.6–1.9, 19% increase), MSM (5.0–11.9, 138% increase) and heterosexual men (2.7–3.2, 18% increase). In 2016, the proportion of UK-born heterosexual women with IS was greater in WIAs (82%) than in NINEAs (81%) and endemic areas (35%;p<0.001). The proportion of MSM identifying as bisexual was greater in WIAs (14%) compared with NINEAs (9%) and endemic areas (5%;p<0.001). Discussion: Increased syphilis transmission among MSM in WIAs may have created opportunities for IS acquisition in women. Health promotion to raise awareness of potential risks of acquiring syphilis during pregnancy is needed.